Predicting, Diagnosing, and Treating Acute and Early HIV Infection in a Public Sector Facility in Eswatini. (15th December 2021) - Kerschberger, Bernhard; Aung, Aung; Mpala, Qhubekani; Ntshalintshali, Nombuso; Mamba, Charlie; Schomaker, Michael; Tombo, Marie Luce; Maphalala, Gugu; Sibandze, Dumile; Dube, Lenhle; Kashangura, Rufaro; Mthethwa-Hleza, Simangele; et al.
Abstract : Background: The lack of acute and early HIV infection (AEHI) diagnosis and care contributes to high HIV incidence in resource-limited settings. We aimed to assess the yield of AEHI, predict and diagnose AEHI, and describe AEHI care outcomes in a public sector setting in Eswatini. Setting: This study was conducted in Nhlangano outpatient department from March 2019 to March 2020. Methods: Adults at risk of AEHI underwent diagnostic testing for AEHI with the quantitative Xpert HIV-1 viral load (VL) assay. AEHI was defined as the detection of HIV-1 VL on Xpert and either an HIV-seronegative or HIV-serodiscordant third-generation antibody-based rapid diagnostic test (RDT) result. First, the cross-sectional analysis obtained the yield of AEHI and established a predictor risk score for the prediction of AEHI using Lasso logistic regression. Second, diagnostic accuracy statistics described the ability of the fourth-generation antibody/p24 antigen–based Alere HIV-Combo RDT to diagnose AEHI (vs Xpert VL testing). Third, we described acute HIV infection care outcomes of AEHI-positive patients using survival analysis. Results: Of 795 HIV-seronegative/HIV-serodiscordant outpatients recruited, 30 (3.8%, 95% confidence interval: 2.6% to 5.3%) had AEHI. The predictor risk score contained several factors (HIV-serodiscordant RDT, women, feeling at risk of HIV, swollen glands, and fatigue) and had sensitivity and specificity of 83.3% and 65.8%, respectively, to predict AEHI. The HIV-Combo RDT had sensitivity and specificity of 86.2% and 99.9%, respectively, to diagnose AEHI. Of 30 AEHI-positive patients, the 1-month cumulative treatment initiation was 74% (95% confidence interval: 57% to 88%), and the 3-month viral suppression (<1000 copies/mL) was 87% (67% to 98%). Conclusion: AEHI diagnosis and care seem possible in resource-limited settings. Abstract : Supplemental Digital Content is Available in the Text.